The effects of cardiac structure, valvular regurgitation, and left ventricular diastolic dysfunction on the diagnostic accuracy of Murray law–based quantitative flow ratio - Yang, Junqing; Huang, Yuming; Li, Xiaoshan; Jia, Qianjun; Deng, Huiliang; Xie, Nianjin; Huang, Meiping; Fei, Hongwen (Frontiers in Cardiovascular Medicine, 2023)
Objective The study aimed to investigate the diagnostic accuracy of Murray law–based quantitative flow ratio (μQFR) from a single angiographic view in patients with abnormal cardiac structure, left ventricular diastolic dysfunction, and valvular regurgitation. Background μQFR is a novel fluid dynamics method for deriving fractional flow reserve (FFR). In addition, current studies of μQFR mainly analyzed patients with normal cardiac structure and function. The accuracy of μQFR when patients had abnormal cardiac structure, left ventricular diastolic dysfunction, and valvular regurgitation has not been clear. Methods This study retrospectively analyzed 261 patients with 286 vessels that underwent both FFR and μQFR prior to intervention. The cardiac structure and function were measured using echocardiography. Pressure wire–derived FFR ≤0.80 was defined as hemodynamically significant coronary stenosis. Results μQFR had a moderate correlation with FFR (r = 0.73, p < 0.001), and the Bland–Altman plot presented no difference between the μQFR and FFR (0.006 ± 0.075, p = 0.192). With FFR as the standard, the diagnostic accuracy, sensitivity, specificity, positive predictive value, and negative predictive value of μQFR were 94.06% (90.65–96.50), 82.56% (72.87–89.90), 99.00% (96.44–99.88), 97.26 (89.91–99.30), and 92.96% (89.29–95.44), respectively. The concordance of μQFR/FFR was not associated with abnormal cardiac structure, valvular regurgitation (aortic valve, mitral valve, and tricuspid valve), and left ventricular diastolic function. Coronary hemodynamics showed no difference between normality and abnormality of cardiac structure and left ventricular diastolic function. Coronary hemodynamics demonstrated no difference among valvular regurgitation (none, mild, moderate, or severe). Conclusion μQFR showed an excellent agreement with FFR. The effect of abnormal cardiac structure, valvular regurgitation, and left ventricular diastolic function did not correlate with the diagnostic accuracy of μQFR. Coronary hemodynamics showed no difference in patients with abnormal cardiac structure, valvular regurgitation, and left ventricular diastolic function.